Advanced Platelet-Rich Fibrin Plus (A-PRF+) as an Additive to Hard Tissue Managing Protocols in Oral Surgery: A Systematic Review - Marek Chmielewski; Andrea Pilloni; Paulina Adamska (Journal of Functional Biomaterials)
Background: Advanced platelet-rich fibrin + (A-PRF+) represents a third generation of autologous platelet derivatives. Appropriate centrifugation conditions cause the formation of a clot containing platelets, which slowly release growth factors that influence healing. The objective of this article was to undertake a review of the available literature on the effectiveness of A-PRF+ use in hard tissue procedures. Materials and methods: In order to ensure the most accurate and relevant results, only randomized clinical trials regarding bone regeneration techniques/bone healing that compared the effect of the A-PRF+ addition in dentistry were included in this study. Articles taken into consideration for the review were published between the beginning of 2014 and 31 December 2024. The search of manuscripts for the review was conducted using the PubMed, Scopus, Google Scholar, and Cochrane databases. For this study, 10 articles focusing on A-PRF+ were qualified. Results: A-PRF+ was found to increase the post-surgical vertical and horizontal alveolar ridge dimensions. The bone formed in the surgical site presented a higher volume of vital and non-vital bone and a more optimal bone composition, at the same time providing a lower percentage of connective tissue inclusions. When combined with other grafting biomaterials, A-PRF+ enhanced their performance and integration. A-PRF+ did not have any significant effect on the mineral bone density compared with other grafting materials. Compared with PRF and other blood derived plasmas rich in growth factors, the performance of A-PRF+ was generally better, but often with no statistical significance. The treatment of periodontal defects measured by the reduction in pocket depth and clinical attachment level also fared better with the A-PRF+ addition, although there was no differences noted between A-PRF+ and biphasic calcium phosphate and xenograft. Finally, the A-PRF+ addition improved the primary implant stability in the evaluated studies. Conclusions: The A-PRF+ addition to the surgical protocols significantly enhanced the healing of the bone and when combined with biomaterials improved their integration and increased the implant insertion torque, improving the primary and secondary stability. It may be a viable alternative for patients that express their concern towards human- and animal-derived biomaterials.